[Book review] Nils-Gustaf Stahre et al., Stockholms gatunamn - Edlund, Lars-Erik (Journal of Northern Studies, 2024)
Review of: Nils-Gustaf Stahre, Per Anders Fogelström, Jonas Ferenius & Gunnar Lundqvist (with participation of Börje Westlund, Lars Wikström, Göran Sidenbladh, Lars Cleve & Carl Magnus Rosell), expanded and revised edition by Staffan Nyström, Stockholms gatunamn, 4th edition, Stockholm: Stockholms stad 2022